Previous Vitamin D Supplementation and Morbidity and Mortality Outcomes in People Hospitalised for COVID19: A Cross-Sectional Study - Arroyo-Díaz, Juan Antonio; Julve, Josep; Vlacho, Bogdan; Corcoy, Rosa; Ponte, Paola; Román, Eva; Navas-Méndez, Elena; Llauradó, Gemma; Franch-Nadal, Josep; Domingo, Pere; Mauricio, Didac (Frontiers in Public Health, 2021)
Aim: The study aim was to assess the association of vitamin D supplementation before hospital admission and severe outcomes in subjects admitted for COVID-19. Methods: We performed a cross-sectional analysis of pseudonymised medical record data from subjects admitted to the Hospital de la Santa Creu i Sant Pau (Barcelona, Spain) for COVID-19 during March and April 2020. The composite primary study outcome was defined as death and/or invasive mechanical ventilation (IMV). Association between risk factors and study outcomes was evaluated by bivariate analysis, followed by logistic regression analysis. Results: In total, 1,267 persons were hospitalised during the observation period. Overall, 14.9% of the subjects were on active vitamin D supplementation treatment before admission. The subjects in the vitamin D group were significantly older than subjects without vitamin D supplementation. We observed higher rates of the primary outcome (death and/or IMV) among the persons with previous use of vitamin D (30.1 vs. 22.9% in those not receiving treatment). In the bivariate analysis, previous use of vitamin D was positively associated with death and/or IMV [odds ratio (OR): 1.45 95% CI: 1.03; 2.04]; however, after adjustment for other risk factors this association disappeared (OR: 1.09 95%CI: 0.65; 1.81). Conclusion: We did not find an association between vitamin D supplementation before hospital admission and death and/or IMV in subjects admitted for COVID-19. The age and the burden of age-associated comorbidities were independently associated with the in-hospital events.